PTU-049 Patients with 'missed' interval colorectal cancers on the national faecal occult blood testing programme may not be truly asymptomatic – results from a multicentre study. (17th June 2017) - George, AT; Aggarwal, S; Dharmavaram, S; Menon, A; Dube, M; Vogler, M; Field, A
Abstract : Introduction: To identify symptomatology of interval cancers(IC-cancers diagnosed within 2 years of a negative Faecal Occult Blood Testing(FOBT)). Method: National Bowel Cancer Audit Programme data from three centres, for all colorectal cancers(CRC)in the screening age group(60–74 years)over a 2 year period(August 2011–2013)were linked for their Faecal Occult Blood Testing(FOBT)screening status( BCSP database/Eastern Hub ).Detailed symptomatology of IC were analysed.Tumours at and beyond splenic flexure were considered left-sided. Results: The study covered 2 million population( 2 00 000 screening eligible). 521 CRC were diagnosed(0.11%). 231 CRC(44%)were in patients who had declined screening, 162 CRC(31%)were screen-detected and 128 CRC(25%)were IC. Of these 128 patients(M: F; 84:44), median age 67 years(SD: 3.8)the commonest presenting symptoms was change in bowel habits in 50 (39%).Others included bleeding per-rectum( 44 (34%)patients, abdominal pain 38 (30%), anaemia 36 (28%), loss of weight 14 (11%), bowel obstruction 13 (10%), bowel perforation in 3 (2%) patients. Only two patients were truly asymptomatic-CRC being identified in oneduring gynaecological surgery and during trauma laparotomy in the other. In the anaemic patients(36 (28%)) the blood picture showed Hb(mean;10.3 gm);MCV( 82.4);MCH(26.3).61% of anaemic patients had CRC in the right colon with an equal percentage being of Duke's stage C/D. The time from negative FOB test to CRC diagnosis was 15 months (0.5–24 months). Conclusion: Our findings highlight majority of IC patients were symptomatic with 'red flag symptoms'. We raise the possibility of a natural bias in patients volunteering for the FOB test in that they may have bowel symptoms not yet discussed with their general practitioner. We highlight the need for improved awareness to reduce delays in symptomatic patients seeking medical advice against a background of a negative FOBT. Disclosure of Interest: None Declared